Role of Homeopathy in Managing COVID-19 Symptoms in Elderly Patients: A Case Series Study - Dr Maneesha Soni (The Bioscan, 2024)
The global healthcare systems are facing a substantial challenge due to the COVID-19 pandemic, particularly concerning elderly patients with concurrent health conditions. This research study outlines the use of homeopathic remedies in managing COVID-19 symptoms among elderly patients. A comprehensive analysis of 116 elderly cases was conducted based on the severity of symptoms and associated health conditions. The study revealed that remedies such as Sulphur, Arsenicum Album, Lycopodium, and Phosphorus demonstrated notable efficacy in addressing severe cases, while Bryonia and Carbo Vegetabilis proved beneficial in alleviating cough and breathlessness, respectively.